Effect of Ti addition on the kinetics and mechanism of non-isothermal and isothermal oxidation of Nb–Si–Mo alloys at 900 °C–1200 °C. (November 2021) - Sala, Kasturi; Kashyap, Sunil Kumar; Mitra, Rahul
Abstract: The effect of 20 at% Ti addition and annealing (1500 °C/100 h) on non-isothermal and isothermal oxidation behavior of as-cast hypoeutectic Nb–12Si–5Mo or hypereutectic Nb–19Si–5Mo alloys has been investigated. On heating to 1300 °C in air, the mass gain begins at lower temperature, with a steeper rise in the ternary alloys, compared to the Ti-containing alloys. On isothermal exposure for 24 h, the ternary alloys have exhibited lower mass gain at 900 °C than the quaternary alloys, but the trend has reversed at 1100 °C and 1200 °C, with the hypereutectic Ti-containing alloy exhibiting the least mass gain. The products of oxidation are found as Nb2 O5 and SiO2, with TiO2, TiNb2 O7 and Ti2 Nb10 O29 being formed additionally in the oxide scales of the Nb–12Si–5Mo–20Ti and Nb–19Si–5Mo–20Ti alloys. Analysis of the oxidation kinetics suggest an initial phase of interface-reaction controlled rapid increase of mass, followed by stage of parabolic behavior, where diffusion of O 2− or Ti 4+ through the oxide scale could be the rate-controlling in ternary or Ti-containing quaternary alloys, respectively. Coarser microstructure obtained by annealing has caused higher mass gain than that observed for the corresponding as cast sample. The as cast or annealed Nb–19Si–5Mo–20Ti alloy has exhibited lower values of parabolic rate constant than other alloys at ≥1100 °C, due to the formation of a defect-free oxide scale. Reduced oxygen solubility and diffusivity due to the presence of Mo and Ti in Nb-solid solution, along with formation of SiO2 -rich oxide on hypereutectic quaternary alloy at 1100 °C and 1200 °C appear to be responsible for their superior oxidation resistance. Highlights: Adding Ti to Nb–Si–Mo alloys improves oxidation resistance in the 1100–1200 °C temperature range. Oxidation forms Nb2 O5 +SiO2 +MoO2 besides TiO2 +TiNb2 O7 +Ti2 Nb10 O29 in Ti-added alloys. Oxidation of hypereutectic alloys is retarded by SiO2 containing oxide scales. Reduced oxygen solubility and diffusivity by Mo + Ti addition retard oxidation rates. Oxidation kinetics is initially interface-reaction controlled and then parabolic.